ChemInform Abstract: Template‐Free Solvothermal Synthesis and Enhanced Thermoelectric Performance of Sb2Te3 Nanosheets. Issue 19 (18th April 2013) - Sun, Shaolin; Peng, Jing; Jin, Renxi; Song, Shuyan; Zhu, Pinwen; Xing, Yan
Abstract Single‐crystalline Sb2Te3 nanosheets are prepared by a simple template‐free solvothermal approach using SbCl3, Na2TeO3, N2H4·H2O, and NH3 in ethylene glycol (autoclave, 473 K, 12 h).